Assessing the Key Predictors of an Academic Career after Craniofacial Surgery Fellowship. Issue 6 (December 2020) - Luby, Alexandra O.; Ranganathan, Kavitha; Matusko, Niki; Buchman, Steven R.
Abstract : Background: As craniofacial fellowship positions outnumber the availability of academic craniofacial jobs, it is important to understand the factors associated with securing an academic position after fellowship. The purpose of this study was to evaluate the impact of bibliometric indices and trainee demographics on the ability to obtain a full-time academic plastic surgery position on completion of a craniofacial fellowship. Methods: Craniofacial fellowship graduates between 2009 and 2018 ( n = 182) were identified. Initial job placement and demographic data were collected; bibliometric indices at fellowship completion were calculated. Chi-square and Fisher's exact tests and multivariable logistic regression were used to assess the association of select factors with job placement. Results: Of the 48.9 percent of fellows that secured academic positions, 39.3 percent trained at five fellowship institutions. The majority of those completing residency at top institutions for academic surgery and research entered academic positions at fellowship completion. Geography influenced academic placement, as 72.7 percent of trainees in the Northeast secured academic positions. Only 20.3 percent of fellows completed dedicated postgraduate research time, but among these, 70.3 percent entered academic jobs. The h -index (OR, 1.14; p = 0.01) and total manuscripts (OR, 1.04; p = 0.02) were significantly associated with academic practice while adjusting for other covariates. Conclusions: Although residency training institution, geographic location, and postgraduate research may influence academic placement, the h -index and total manuscripts represent the best predictors of academic careers after craniofacial fellowship. This information is valuable for applicants who aspire to be academic craniofacial surgeons, and for programs and educators who can use these data to identify applicants with a propensity for academics. Abstract : Supplemental Digital Content is available in the text.